2017
DOI: 10.1038/srep41650
|View full text |Cite
|
Sign up to set email alerts
|

Low-density lipoprotein cholesterol and survival in pulmonary arterial hypertension

Abstract: Low-density lipoprotein cholesterol(LDL-C) is a well established metabolic marker of cardiovascular risk, however, its role in pulmonary arterial hypertension (PAH) has not been determined. Therefore we assessed whether LDL-C levels are altered in PAH patients, if they are associated with survival in this group and whether pulmonary hypertension (PH) reversal can influence LDL-C levels. Consecutive 46 PAH males and 94 females were age matched with a representative sample of 1168 males and 1245 females, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 50 publications
3
32
0
2
Order By: Relevance
“…In agreement with this finding, Kopec et al reported recently significantly lower LDL levels in PAH patients, including those with connective tissue diseases, compared to controls, and lower LDL levels were significantly associated with high mortality rate from PAH [36]. Moreover, the reversal of chronic thromboembolic PAH has raised levels of LDL compared to unchanged levels in patients with non-reversed chronic thromboembolic PAH [36]. Unexpectedly, there was no association between the presence of vasculitis or Raynaud's phenomenon and PAH.…”
Section: Discussionsupporting
confidence: 65%
“…In agreement with this finding, Kopec et al reported recently significantly lower LDL levels in PAH patients, including those with connective tissue diseases, compared to controls, and lower LDL levels were significantly associated with high mortality rate from PAH [36]. Moreover, the reversal of chronic thromboembolic PAH has raised levels of LDL compared to unchanged levels in patients with non-reversed chronic thromboembolic PAH [36]. Unexpectedly, there was no association between the presence of vasculitis or Raynaud's phenomenon and PAH.…”
Section: Discussionsupporting
confidence: 65%
“…We collected venous blood from each participant after 12 h of fasting on the day of hemodynamic assessment. Complete lipid profile was assessed using the direct colorimetric method, as described previously [5]. Insulin concentration was assessed using electro-chemiluminescence immunoassay (Roche, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…Recent clinical studies found alterations in lipid profile, such as elevated triglyceride (TG)-to-high-density lipoprotein cholesterol (HDL-C) ratio and lowered HDL-C, to be more prevalent in pulmonary arterial hypertension (PAH) patients than in age-matched controls [4,5]. Both of them were associated with poor survival [4] and worse clinical status in this population [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kopec et al . () reported that the serum concentration of LDLs is associated with increased mortality. These data suggest that the serum HDL or LDL levels in PAH patients is indicative of the severity and survivability of PAH.…”
Section: Vascular Function In Dyslipidaemiamentioning
confidence: 99%